Comment on the paper of Mostafa M. A. Khater et al. [Superlattices and Microstructures, 113 (2018) 346–358]. (November 2018) - Zayed, Elsayed M.E.; Al-Nowehy, Abdul-Ghani
Abstract: This comment concerns the doubtful new auxiliary equation method (Khater method) included in the above paper. We prove by simple calculation that this method is wrong. The exact solutions of the proposed nonlinear equation obtained in the above paper are all wrong. Highlights: The new auxiliary equation method is called Khater method. We prove by simple calculation that Khater method is wrong. We show that the exact solutions obtained in the above paper are all wrong.